Laminated structure

By combining polypropylene resins and/or polyethylene resin surface slices in the two sides of the hollow plate core, the problem of insufficient mechanical strength in the existing layer of stacking structures is solved. Low layered structure.

CN119365330APending Publication Date: 2025-01-24TBM CO LTD
View PDF 19 Cites 0 Cited by

Patent Information

Application Number
CN202380047430.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-22
Filing Date
2023-04-11
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

In the conventional laminated structure based on general resins, the hollow core structure is insufficient mechanical strength, and the non-generic resin has low moldability and high cost.

Method used

The polypropylene resin and/or polyethylene resin composition with high -filling of inorganic substance powder and/or polyethylene resin are used as materials for the hollow plate -shaped core, and the polypropylene resin and/or polyethylene resin are fitted on both sides. Surface sheet.

Benefits of technology

The layered structures that have excellent mechanical characteristics such as strength, easy to mold, and presented good appearance, reducing costs and improving the generality.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119365330A_ABST
    Figure CN119365330A_ABST
Patent Text Reader

Abstract

The purpose of the present invention is to provide a laminated structure which has excellent mechanical characteristics such as strength, is easy to mold, and exhibits a good appearance. A laminated structure in which surface sheets comprising a thermoplastic resin are bonded to both surfaces of a hollow plate-like body core in which hollow plate-like bodies are arranged in the thickness direction, the hollow plate-like body core comprising a polypropylene resin and / or a polyethylene resin and an inorganic substance powder, and the surface sheets comprising a thermoplastic resin are bonded to both surfaces of the hollow plate-like body core. The mass ratio of the polypropylene-based resin and / or the polyethylene-based resin to the inorganic substance powder is 10: 90 to 50: 50, and the surface sheet is composed of a polypropylene-based resin and / or a polyethylene-based resin.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a laminated structure. Background Art

[0002] Conventionally, laminated structures having a core of a hollow plate-like body in a shape of a honeycomb, a hollow cylinder, a corrugated shape, a harmonica shape, etc., have been used as consumer goods, industrial products, and items for transportation vehicles such as automobiles and aircraft.

[0003] The strength per unit mass of the hollow plate-like body represented by the honeycomb core is extremely large. In particular, the hollow plate-like body with a resin matrix can form a lightweight and high-strength material, which is useful as aircraft parts, etc. In addition, when the hollow plate-like body is damaged by a strong external force, it also absorbs energy through the buckling of the hollow cells, so it can be used as an impact absorbing material. The stacked structure with sheets bonded to both sides of the hollow plate-like body core has many air-containing cells, so the thermal conductivity is low and it is useful as a heat insulating material. In addition, such a stacked structure also exerts a sound absorbing effect by opening small holes on the surface of the sheet. Therefore, the hollow plate-like body and the stacked structure based on it are mostly used as consumer products such as containers, racks, pallets, panels, bags, and industrial products such as heat insulating materials, sound absorbing materials, filters, and impact absorbing materials (for example, patent documents 1 to 6).

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Publication No. 2010-247448

[0007] Patent Document 2: Japanese Patent Application Publication No. 2013-233796

[0008] Patent Document 3: Japanese Patent Application Publication No. 2018-108740

[0009] Patent Document 4: Japanese Patent Application Publication No. 2017-65810

[0010] Patent Document 5: Japanese Patent Application Laid-Open No. 6-320652

[0011] Patent Document 6: Japanese Patent Application Publication No. 2021-53899 Summary of the invention

[0012] Problem that the invention aims to solve

[0013] However, the laminated structures based on the hollow plate-like body, especially the laminated structures based on general-purpose resins described in Patent Documents 1 to 4, may have the problem of insufficient mechanical strength due to the hollow core structure. Such a problem can be avoided by using a resin with high mechanical strength for the hollow plate-like body as described in Patent Documents 5 and 6, but such resins have low versatility and are disadvantageous in terms of cost. In addition, the moldability of non-general-purpose resins is often low, which sometimes has an adverse effect on the appearance of the obtained hollow plate-like body and its laminated structure.

[0014] The present invention has been made in view of the above-mentioned actual circumstances, and an object of the present invention is to provide a laminated structure which is excellent in mechanical properties such as strength, is easy to mold, and exhibits a good appearance.

[0015] Solutions to the problem

[0016] The inventors of the present invention have obtained the following insights: if a laminated structure is formed by bonding surface sheets composed of a polypropylene resin and / or a polyethylene resin composition to both sides of a hollow plate-like core composed of a polypropylene resin and / or a polyethylene resin composition highly filled with inorganic substance powder, the laminated structure has excellent mechanical properties and molding processability and presents a good appearance. More specifically, the present invention provides the following technical solutions.

[0017] (1) A laminated structure comprising surface sheets made of thermoplastic resin bonded to both surfaces of a hollow plate-like core, wherein the hollow plate-like core has hollow plate-like bodies arranged in a thickness direction, wherein:

[0018] The hollow plate-like core comprises polypropylene resin and / or polyethylene resin and inorganic powder, wherein the mass ratio of the polypropylene resin and / or polyethylene resin to the inorganic powder is 10:90 to 50:50, and

[0019] The surface sheet is made of a polypropylene resin and / or a polyethylene resin.

[0020] (2) The laminated structure according to (1), wherein the hollow plate-like core contains lauric acid diethanolamide, and a content of the lauric acid diethanolamide is 0.1% by mass or more and 1.0% by mass or less relative to the total mass of the hollow plate-like core.

[0021] (3) A laminated structure according to (1) or (2), wherein the polyethylene resin in the hollow plate core comprises a high-density polyethylene and a linear low-density polyethylene, and the mass ratio of the high-density polyethylene to the linear low-density polyethylene is 90:10 to 50:50, the melt mass flow rate (MFR) (190°C, 2.16 kg) of the high-density polyethylene measured in accordance with Japanese Industrial Standard JIS K 6922-1 (ISO1133) is 5 g / 10 min or more and 15 g / 10 min or less, and the MFR (190°C, 2.16 kg) of the linear low-density polyethylene measured in accordance with Japanese Industrial Standard JIS K 6922-1 (ISO1133) is 0.5 g / 10 min or more and 1.5 g / 10 min or less.

[0022] (4) The laminated structure according to any one of (1) to (3), wherein the polypropylene-based resin of the hollow plate-like core is a polypropylene homopolymer and / or a propylene block polymer.

[0023] (5) The laminated structure according to any one of (1) to (4), wherein the hollow plate-like core contains both the polypropylene-based resin and the polyethylene-based resin.

[0024] (6) The laminate structure according to any one of (1) to (5), wherein the surface sheet is a polypropylene-based resin sheet.

[0025] (7) The laminated structure according to any one of (1) to (6), wherein the inorganic substance powder is heavy calcium carbonate.

[0026] (8) The laminated structure according to (7), wherein the average particle size of the heavy calcium carbonate is 0.7 μm or more and 6.0 μm or less.

[0027] (9) The laminate structure according to any one of (1) to (8), wherein the hollow plate-like core and the surface sheet are bonded together via an adhesive layer.

[0028] (10) The laminated structure according to any one of (1) to (9), wherein the hollow plate-like core is selected from the group consisting of a honeycomb core, a hollow cylindrical core, a wavy corrugated core, and a harmonica core.

[0029] (11) A panel comprising the laminated structure according to any one of (1) to (10).

[0030] Effects of the Invention

[0031] According to the present invention, there can be provided a laminated structure which is excellent in mechanical properties such as strength, is easy to mold and process, and exhibits a good appearance, and a panel composed of the laminated structure. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 The following are schematic cross-sectional views showing some embodiments of the laminated structure of the present invention. DETAILED DESCRIPTION

[0033] Hereinafter, embodiments of the present invention will be described, but the present invention is not limited thereto.

[0034] 《Layered Structure》

[0035] The stacked structure of the present invention is a stacked structure formed by bonding surface sheets composed of thermoplastic resin to both surfaces of a hollow plate-like core, in which hollow plate-like cores are arranged along the thickness direction, wherein the hollow plate-like core contains polypropylene resin and / or polyethylene resin and inorganic material powder in a specific mass ratio, and the surface sheets are composed of polypropylene resin and / or polyethylene resin.

[0036] Figure 1 It is a cross-sectional schematic diagram showing several embodiments of the stacked structure of the present invention. In the stacked structure 1 of the present invention, "arranged with hollow plate-like bodies arranged in the thickness direction" refers to the following arrangement: the side surfaces of the hollow hexagonal prisms (honeycombs) and hollow cylinders constituting the hollow plate-like body core 2 extend in the thickness direction of the stacked structure 1, and the two end opening surfaces of the hollow hexagonal prisms and hollow cylinders are oriented in a direction perpendicular to the side surfaces, i.e., the two main surface sides of the stacked structure. Therefore, in the stacked structure 1 of the present invention, each opening surface in the hollow plate-like body core 2 is connected to the surface sheets 3 and 4 at both ends.

[0037] exist Figure 1 In the stacked structure 1 shown, the hollow plate-like core 2 is Figure 1 a is a honeycomb core based on hexagonal prisms. Figure 1 b is a hollow cylindrical core. Figure 1 c is a wave-shaped corrugated core. Figure 1 d is a harmonica-shaped core based on a square prism. Figure 1 The structure in which the hollow plate-like bodies are arranged in the thickness direction as shown in a to 1d has a very high strength per unit mass, and becomes a laminated structure suitable for aircraft parts, etc. It is also easy to show the characteristics of a shock absorbing material or a heat insulating material, and the sound absorbing effect when small holes are opened on the surface of the surface sheet 3 and / or the surface sheet 4 is also increased.

[0038] There is no particular restriction on the shape and size of the stacked structure 1, and it can be made into a desired shape and size corresponding to the purpose and use. For example, it can be a flat plate shape extending to several meters in length and width, or it can be made into a flat plate shape with a width of several millimeters. Depending on the purpose, it can also be made into a non-flat plate shape with concave-convex or curved. There is no particular restriction on the thickness of the stacked structure 1, for example, it can be set to several millimeters to tens of centimeters. In addition, multiple stacked structures 1 can also be joined or stacked.

[0039] In the case where a stacked structure 1 is required to have a large thickness, it is preferred to manufacture a plurality of so-called preforms having a thickness of, for example, about 2 to 50 mm, particularly about 5 to 25 mm, and stack the plurality of preforms to a target thickness from the viewpoint of strength or ease of manufacture. At this time, the stacked structures 1 having surface sheets 3 and surface sheets 4 attached to both sides of each hollow plate-like core 2 may be stacked on each other, or a structure in which the surface sheets of the stacked portion are provided as only one sheet may be made, such as a first surface sheet 3-first hollow plate-like core 2-second surface sheet 3-second hollow plate-like core 2-second surface sheet 4. In addition, preforms having different structures of the hollow plate-like core 2 may be stacked, such as Figure 1 The laminated structural material of the honeycomb core shown in a is similar to that of Figure 1 The stacked structural material of the wave-type corrugated core shown in c is stacked, etc.

[0040] There is no particular restriction on the pitch (repeating interval) of the hexagonal prisms or cylinders constituting the hollow plate-like core 2. For example, it can be a honeycomb structure in which regular hexagonal prisms with a side of about 0.2 to 10 mm (diagonal distance 0.4 to 20 mm), especially about 1 to 6 mm (diagonal distance 2 to 12 mm) are continuously connected, or it can be a hollow cylindrical structure in which cylinders with a diameter of about 0.4 to 20 mm, especially about 2 to 12 mm, are connected to each other. It should be noted that the wall thickness (thickness of the non-void portion) of these hexagonal prisms and cylinders can be set to about 50 to 2000 μm, especially about 100 to 1000 μm, for example.

[0041] The thickness of the surface sheet 3 and the surface sheet 4 is not particularly limited. For example, it can be set to 5 to 1000 μm, further set to 20 to 800 μm, and particularly set to a thickness of about 100 to 500 μm. In addition, the surface sheet 3 and the surface sheet 4 can be the same thickness or different thicknesses. These surface sheets are sometimes attached to the hollow plate-like body core 2 by an adhesive layer according to expectations, and the thickness of the adhesive layer in this case is not particularly limited. It is also possible to coat or further attach other sheets or films on the surface of the surface sheet 3 and / or the surface sheet 4 to make a multilayer structure.

[0042] <Hollow plate body core>

[0043] As described above, the hollow plate-like body core in the laminated structure of the present invention has a structure in which the hollow plate-like bodies are arranged in the thickness direction and contains polypropylene resin and / or polyethylene resin and inorganic substance powder in a mass ratio of 10:90 to 50:50. After in-depth research, the inventors found that: First, by making the hollow plate-like body core into the structure and composition as described above, although a low-cost general-purpose resin is used as the matrix, a laminated structure with excellent mechanical properties such as strength, easy molding and good appearance can be obtained. The following is an explanation of the raw materials constituting the hollow plate-like body core.

[0044] [Polypropylene resin]

[0045] The polypropylene resin in the present invention is not particularly limited as long as it is a resin containing repeating units of propylene in at least a portion. For example, the polypropylene resin in the present invention includes a resin containing propylene component units of 50% by mass or more, particularly 60% by mass or more. As an example, a propylene homopolymer or a copolymer of propylene and other monomers copolymerizable therewith (propylene copolymer) etc. can be cited. These polypropylene resins can be used alone or in combination of two or more.

[0046] There is no particular restriction on the molecular weight of the polypropylene resin. For example, a resin having a mass average molecular weight of 50,000 or more and 500,000 or less, particularly a resin having a mass average molecular weight of 100,000 or more and 400,000 or less, can be used, but it is not limited thereto. Generally speaking, the higher the molecular weight, the better the mechanical properties such as strength, and the lower the molecular weight, the better the moldability. A polypropylene resin having a mass average molecular weight of 50,000 or more and less than 200,000 or less and a polypropylene resin having a mass average molecular weight of 200,000 or more and 500,000 or less can also be used in combination. By using polypropylene resins of different molecular weights in combination, it is also possible to improve moldability and reduce the poor appearance of molded products.

[0047] In addition, the melting properties such as melt mass flow rate (MFR) of the polypropylene resin can be any melting properties. For example, a resin having an MFR (230°C) of about 0.3 to 3.0 g / 10 minutes can be used. In addition, a resin having an MFR (230°C) of 1.0 to 3.0 g / 10 minutes and a melt tension (230°C) of 5 to 30 g and a resin having an MFR (230°C) of 0.3 to 1.0 g / 10 minutes can be used in combination. By using polypropylene resins with different melting properties in combination, molding processability can also be improved.

[0048] The copolymer of propylene and other monomers may be a random copolymer or a block copolymer, and further, may be not only a binary copolymer but also a ternary copolymer. As copolymer components (other monomers), tetrafluoroethylene and vinyl acetate may be cited, but are not limited thereto.

[0049] In the present invention, it is preferred to use a propylene homopolymer, or a copolymerized resin containing a small amount (e.g., less than 5% by mass) of other monomers, and / or a propylene block polymer. It should be noted that even in a propylene homopolymer, as a result of polymerization, a structure that is copolymerized with, for example, α-olefins such as hexene may be included in part, and in the present invention, such a polymer is also widely included as a propylene homopolymer.

[0050] (Propylene homopolymer)

[0051] Propylene homopolymer (hereinafter sometimes referred to as "PP") is a polymer obtained by substantially polymerizing only propylene, and has excellent rigidity and heat resistance. Various products are commercially available, and examples thereof include: WINTEC (registered trademark) and NOVATEC (registered trademark) of Japan Polypropylene Co., Ltd., NOBLEN (registered trademark) of Sumitomo Chemical Co., Ltd., Prime Polypro (registered trademark) of Pu Ruiman Polymer Co., Ltd., TORAYCA (registered trademark) of Toray Industries, Ltd., SABIC (registered trademark) PP of Saudi Basic Petrochemicals (SABIC Petrochemicals), and SunAllomer (registered trademark) of SunAllomer Co., Ltd. However, the present invention is not limited to these, and any PP may be included. Multiple PPs may also be used in combination.

[0052] According to the difference of stereoregularity, propylene homopolymer is classified into isotactic PP, syndiotactic PP, atactic PP, semi-isotactic PP, etc. The laminated sheet of the present invention may contain any one of the above-mentioned propylene homopolymers, and may also have a branched structure, such as a long-chain branched structure. In addition, it may be a structure with a high stereoregularity of, for example, 90% or more of the isotactic triad fraction (mm), or a propylene homopolymer with an atactic structure, or a propylene homopolymer containing trace components produced as by-products during polymerization. It is also possible to use a plurality of these propylene homopolymers in combination.

[0053] (propylene block copolymer / propylene block polymer)

[0054] Propylene block copolymer is a copolymer composed of continuous blocks of propylene monomer and continuous blocks of other monomer components. Here, there is no particular restriction on the monomer components copolymerized with propylene, and the block copolymer is not limited to binary system, and can also be ternary system, quaternary system, etc. There is no particular restriction on the copolymerization ratio of each monomer, the length of each block, the overall molecular weight, etc. In the present invention, preferably a block copolymer composed of propylene and other α-olefins, etc. If it is a block copolymer of propylene and α-olefin, it can form a laminated structure with better mechanical properties and moldability.

[0055] Block copolymers of propylene and α-olefins are well known and are commercially available in various varieties. As examples, NOVATEC (registered trademark) of Japan Polypropylene Co., Ltd., Prime Polypro (registered trademark) of Prime Polymer Co., Ltd., UMEX (registered trademark) of Sanyo Chemical Industries, Ltd., and SunAllomer (registered trademark) of SunAllomer Co., Ltd. are listed, but the present invention is not limited to these and may include any propylene block copolymer. Two or more block copolymers may also be used in combination. There is no particular restriction on the monomer copolymerized with propylene, for example, it may be one or more monomer components selected from ethylene and α-olefins having 4 to 10 carbon atoms. As examples, ethylene, 1-butene, isobutylene, 1-pentene, 3-methyl-1-butene, 1-hexene, 3,4-dimethyl-1-butene, 1-heptene, 3-methyl-1-hexene, 1-octene, etc. are listed, but are not limited to these.

[0056] Among these block copolymers, copolymers with ethylene, 1-butene, isobutylene, 1-hexene and / or 1-octene are preferred, and copolymers with ethylene are particularly preferred. There are no particular restrictions on the copolymerization ratio and molecular weight, and copolymers such as the following can be used: preferably copolymers with a structural unit of α-olefin as a comonomer of 5% by mass or more, more preferably copolymers with a structural unit of 7% by mass or more, and particularly preferably copolymers with a structural unit of 8% by mass or more; in addition, copolymers with a structural unit of 35% by mass or less are preferred, copolymers with a structural unit of 25% by mass or less are more preferred, copolymers with a structural unit of 20% by mass or less are further preferred, and copolymers with a structural unit of 18% by mass or less are particularly preferred. These block copolymers are rich in flexibility and therefore show particularly excellent mechanical properties and molding processability.

[0057] The block copolymer has various properties, for example, a mass average molecular weight of 20,000 to 5,000,000, typically 50,000 to 1,000,000, and particularly 70,000 to 400,000; a density of 0.84 to 0.92 g / cm 3 , typically 0.85 to 0.91 g / cm 3The crystallinity will be 0.5-40%, typically in the range of about 5-25%; the melt flow rate (MFR measured according to ASTM D1238 at 2.16 kg and 230° C.) will be 0.1-90 g / 10 min, typically in the range of about 0.5-30 g / 10 min; the melting temperature will be 120-180° C., typically 150-170° C., particularly in the range of about 160-165° C., but are not limited to these. In the present invention, propylene-α-olefin copolymers of any characteristics may also be used.

[0058] In the present invention, preferably, the block copolymer is a propylene-ethylene block copolymer composed of a propylene block and an ethylene-propylene copolymer block. More preferably, a block copolymer is used in which the structural unit derived from propylene is 80% by mass or more and the structural unit derived from ethylene is 20% by mass or less; particularly preferably, a block copolymer is used in which the structural unit derived from propylene is 82-92% by mass and the structural unit derived from ethylene is 8-18% by mass; and most preferably, a block copolymer is used in which the structural unit derived from propylene is 84-90% by mass and the structural unit derived from ethylene is 10-16% by mass.

[0059] Propylene-ethylene block copolymers as described above, for example, can be manufactured by polymerizing propylene alone and then copolymerizing ethylene, and are also referred to as propylene block polymers or block polypropylene. Generally speaking, in propylene-ethylene block polymers, a so-called sea island structure in which ethylene blocks or ethylene-propylene copolymer block phases are dispersed in a continuous phase completely polymerized by propylene is shown. Generally speaking, ethylene-propylene copolymers are soft, and therefore bring flexibility to the hollow plate-like body core. Therefore, if used in the present invention, a laminated structure having more excellent molding processability, appearance and mechanical properties can be provided.

[0060] [Polyethylene resin]

[0061] The polyethylene resin in the present invention is not particularly limited as long as it is a resin containing repeating units of ethylene in at least a portion. For example, the polyethylene resin in the present invention includes a resin containing ethylene component units greater than 50% by mass, particularly greater than 70% by mass. One polyethylene resin may be used alone or in combination of two or more. The source of the polyethylene resin is not particularly limited, and may be a synthetic resin or a resin made from raw materials of plant origin.

[0062] Examples of the polyethylene resin include the following.

[0063] High-density polyethylene (HDPE): 0.942 g / cm 3 Polyethylene with density above

[0064] Medium density polyethylene: 0.930g / cm 3 Above and less than 0.942g / cm 3 Density Polyethylene

[0065] Low-density polyethylene (LDPE): 0.910 g / cm 3 Above and less than 0.930g / cm 3 Density Polyethylene

[0066] Linear low-density polyethylene (LLDPE): 0.911 g / cm 3 Above and less than 0.940g / cm 3 Linear polyethylene

[0067] Ultra-low density polyethylene (ULDPE): less than 0.910 g / cm 3 Density Polyethylene

[0068] The polyethylene resin in the present invention also includes polyethylene resin containing functional groups (ethylene-vinyl acetate copolymer, ethylene-acrylic acid copolymer, ethylene-methacrylic acid copolymer, metal salt (ionomer) of ethylene-methacrylic acid copolymer, ethylene-alkyl acrylate copolymer, ethylene-alkyl methacrylate copolymer, maleic acid modified polyethylene, etc.).

[0069] From the viewpoint of easily exerting the effects of the present invention, preferably, the polyethylene resin contains both the following high-density polyethylene and linear low-density polyethylene. More preferably, the mass ratio of the high-density polyethylene to the linear low-density polyethylene is 90:10 to 50:50, further preferably 85:15 to 55:45, and particularly preferably 80:20 to 60:40. It should be noted that "MFR" is an abbreviation for "melt mass flow rate".

[0070] High-density polyethylene having an MFR (190°C, 2.16 kg) of 5 g / 10 min or more and 15 g / 10 min or less as measured in accordance with JIS K 6922-1 (ISO 1133)

[0071] · Linear low-density polyethylene having an MFR (190°C, 2.16 kg) of 0.5 g / 10 min or more and 1.5 g / 10 min or less as measured in accordance with JIS K 6922-1 (ISO 1133)

[0072] [Inorganic substance powder]

[0073] The inorganic powder in the present invention includes any component that can be added together with the resin, for example, a substance known as a filler can be used appropriately. The inorganic powder can be used alone or in combination of two or more. The inorganic powder includes both synthetic substances and substances derived from natural minerals (crushed substances of minerals, etc.).

[0074] Examples of the inorganic substance powder include powders of salts (carbonates, sulfates, silicates, phosphates, borates), oxides, or hydrates of metals (calcium, magnesium, aluminum, titanium, iron, zinc, etc.).

[0075] Specific examples include powders of calcium carbonate, magnesium carbonate, zinc oxide, titanium oxide, silicon oxide, aluminum oxide, clay, talc, kaolin, aluminum hydroxide, magnesium hydroxide, aluminum silicate, magnesium silicate, calcium silicate, aluminum sulfate, magnesium sulfate, calcium sulfate, magnesium phosphate, barium sulfate, silica sand, carbon black, zeolite, molybdenum, diatomaceous earth, sericite, volcanic ash, calcium sulfite, sodium sulfate, potassium titanate, bentonite, wollastonite, dolomite, and graphite.

[0076] The shape of the inorganic substance powder is not particularly limited, and may be any of particle shape (spherical, irregular shape, etc.), flake shape, granular shape, fibrous shape, and the like.

[0077] The lower limit of the particle size of the inorganic substance powder is not particularly limited, but the average particle size is preferably 0.7 μm or more, and more preferably 1.0 μm or more. The upper limit of the particle size of the inorganic substance powder is not particularly limited, but the average particle size is preferably 6.0 μm or less, and more preferably 5.0 μm or less. In the present invention, the "average particle size" refers to a value calculated based on the measurement result of the specific surface area measured by the air permeation method based on JIS M-8511. As a measuring instrument for the average particle size, for example, a specific surface area measuring device "SS-100" manufactured by Shimadzu Corporation can be preferably used.

[0078] (Heavy Calcium Carbonate)

[0079] Preferably, the inorganic substance powder in the present invention comprises calcium carbonate, especially heavy calcium carbonate, and more preferably, is entirely composed of heavy calcium carbonate.

[0080] In the present invention, "heavy calcium carbonate" refers to calcium carbonate obtained by mechanically crushing natural calcium carbonate, etc., and is clearly distinguished from synthetic calcium carbonate (i.e., light calcium carbonate) produced by chemical precipitation reaction, etc. Heavy calcium carbonate is obtained, for example, by crushing and classifying natural calcium carbonate such as calcite (limestone, chalk, marble, etc.), shells, corals, etc.

[0081] It is known that heavy calcium carbonate includes particles with a wide particle size range and generally has poor molding processability. However, according to the present invention, even a hollow plate-like body core including heavy calcium carbonate has good molding processability and the appearance of the molded product can also be excellent.

[0082] As the pulverizing method in the manufacture method of heavy calcium carbonate, any one of wet pulverizing and dry pulverizing can be adopted. From the viewpoint of economy, dry pulverizing without dehydration process and drying process etc. is preferred. The pulverizer used in the pulverization of heavy calcium carbonate is not particularly limited, and impact pulverizer, pulverizer using pulverizing media (ball mill etc.), roller mill etc. can be cited. The classification in the manufacture method of heavy calcium carbonate can adopt the previously known methods such as air classification, hydrocyclone, decanter etc.

[0083] The ground calcium carbonate may or may not be subjected to surface treatment. The surface treatment may be performed at any time point in the method for producing the ground calcium carbonate (before pulverization, during pulverization, before classification, after classification, etc.).

[0084] Examples of the surface treatment of heavy calcium carbonate include physical methods (plasma treatment and the like) and chemical methods (methods using coupling agents, surfactants and the like).

[0085] In the surface treatment of heavy calcium carbonate, examples of coupling agents used in chemical methods include silane coupling agents and titanium coupling agents.

[0086] Among the surface treatments of heavy calcium carbonate, as the surfactants used in the chemical method, anionic surfactants, cationic surfactants, nonionic surfactants and amphoteric surfactants can be listed. More specifically, for example, higher fatty acids, higher fatty acid esters, higher fatty acid amides, higher fatty acid salts, etc. can be listed.

[0087] By performing the surface treatment as described above, the dispersibility of the heavy calcium carbonate can be improved, etc. However, the heavy calcium carbonate that has not been surface treated is preferred because the risk of odor generation caused by thermal decomposition of the surface treatment agent during molding can be reduced.

[0088] The form of heavy calcium carbonate is not particularly limited, but is preferably in the form of particles from the viewpoint of good dispersibility in the hollow plate-like core.

[0089] When the heavy calcium carbonate is in the form of particles, the average particle size is preferably 0.7 μm to 6.0 μm, more preferably 1.0 μm to 5.0 μm, and further preferably 1.5 μm to 3.0 μm. In addition, preferably, particles with a particle size of 45 μm or more are not included in the particle size distribution.

[0090] If the average grain size of heavy calcium carbonate is in the above-mentioned scope, then the dispersibility in the hollow plate-like body core is good, and the excessive viscosity when can preventing the manufacturing stacking structure body rises. Further, heavy calcium carbonate particles are difficult for protruding and falling off from the surface of the hollow plate-like body core or the stacking structure body, or are difficult for damaging surface texture or mechanical strength etc., and are more likely to bring into play the effect of the present invention.

[0091] When heavy calcium carbonate is particulate, its amorphous property can be represented by the spherical degree of shape, i.e., roundness. The lower the roundness, the higher the amorphous property. When heavy calcium carbonate is particulate, its roundness is preferably more than 0.50 and less than 0.95, more preferably more than 0.55 and less than 0.93, further preferably more than 0.60 and less than 0.90.

[0092] In the present invention, "roundness" refers to the value obtained by dividing the projected area of ​​a particle by the area of ​​a circle having the same circumference as the projected circumference of the particle ((projected area of ​​the particle) / (area of ​​a circle having the same circumference as the projected circumference of the particle)). The method for measuring roundness is not particularly limited, and for example, it can be determined by analyzing the projection image of the particle obtained with a scanning microscope or a stereo microscope using commercially available image analysis software. Specifically, it can be calculated based on the measurement results of the projected area (A) of the particle, the area (B) of the circle having the same circumference as the projected circumference of the particle, the radius (r) of the circle having the same circumference as the projected circumference of the particle, and the projected circumference (PM) of the particle by the following formula.

[0093] “Roundness” = A / B = A / πr 2 =A×4π / (PM) 2

[0094] [Material of the hollow plate core]

[0095] As described above, the hollow plate-like body core in the present invention contains polypropylene resin and / or polyethylene resin and inorganic powder, and the mass ratio of polypropylene resin and / or polyethylene resin to inorganic powder is 10:90 to 50:50. Here, the hollow plate-like body core may contain both polypropylene resin and polyethylene resin as resin components. In the case where the hollow plate-like body core contains polypropylene resin and polyethylene resin, the mass ratio of polypropylene resin: polyethylene resin is preferably about 50:50 to 95:5, and particularly preferably about 55:45 to 90:10.

[0096] More preferably, about 5.0 to 47.5 mass %, especially about 5.5 to 45.0 mass % of polypropylene resin, and / or about 0.5 to 25.0 mass %, especially about 1.0 to 22.5 mass % of polyethylene resin, and about 50.0 to 90.0 mass %, especially about 55.0 to 80.0 mass % of inorganic powder, especially heavy calcium carbonate, are contained relative to the total mass of the hollow plate-like body core. If desired, for example, about 0.1 to 5.0 mass %, especially about 3.0 mass % of components other than these may be contained relative to the total mass of the hollow plate-like body core.

[0097] [Lauryl diethanolamide]

[0098] Preferably, in addition to the above-mentioned raw materials, the hollow plate-like body core in the present invention also contains lauric acid diethanolamide. Lauric acid diethanolamide functions as a surfactant or antistatic agent and is formulated into various cosmetics or resin products. In the hollow plate-like body core constituting the present invention, static electricity during molding is easily prevented by containing lauric acid diethanolamide, and the miscibility of each component becomes better, and the moldability and mechanical properties can be further improved. In addition, the improvement effect of moldability and mechanical properties brought by lauric acid diethanolamide is generally greater than other antistatic agents and surfactants such as quaternary ammonium salts and polyoxyethylene alkylamines. Relative to the total mass of the hollow plate-like body core, the content of lauric acid diethanolamide is preferably set to 0.1% by mass or more and 1.0% by mass or less, wherein it is more preferably set to 0.2% by mass or more and less than 1.0% by mass, and particularly preferably set to 0.3% by mass or more and 0.8% by mass or less.

[0099] The hollow plate-like core in the present invention can, for example, be composed of a polypropylene resin, a polyethylene resin, an inorganic powder and lauric acid diethanolamide, wherein the mass ratio of the sum of the polypropylene resin and the polyethylene resin to the inorganic powder is 10:90 to 50:50, and the content of lauric acid diethanolamide is greater than 0.1 mass % and less than 1.0 mass % relative to the total mass of the hollow plate-like core.

[0100] [Other components in the hollow plate core]

[0101] In the hollow plate-like body core in the stacked structure of the present invention, in addition to the above-mentioned components, any components may be further included within the scope of not hindering the effect of the present invention. Such components may be used alone or in combination of two or more. In addition, the type or amount of such components may be appropriately set according to the desired effect, etc.

[0102] As components that may be included in the hollow plate core, there are listed: lubricants, dispersants, plasticizers and softeners, resins other than polypropylene resins and polyethylene resins, antistatic agents or surfactants other than lauric acid diethanolamide, colorants, antioxidants and other anti-deterioration agents, flame retardants, foaming agents, etc.

[0103] (Lubricant)

[0104] As the lubricant, any lubricant that can be formulated into a general-purpose resin composition can be used, and examples thereof include paraffin wax, sorbitan ester, glycerol ester, zinc stearate, magnesium stearate, and stearamide.

[0105] (Dispersant)

[0106] Examples of the dispersant include long-chain fatty acids such as stearic acid, sodium polyacrylate, polyglycerol fatty acid esters, and sorbitan fatty acid esters.

[0107] (Plasticizer)

[0108] Examples of the plasticizer include acetyl tributyl citrate, triethyl citrate, acetyl triethyl citrate, dibutyl phthalate, diaryl phthalate, dimethyl phthalate, diethyl phthalate, di-2-methoxyethyl phthalate, dibutyl tartarate, o-benzoylbenzoate, diacetin, epoxidized soybean oil, and polyethylene wax.

[0109] (Softener)

[0110] As softeners, hydrocarbon oils such as paraffin oil, naphthenic oils, and aromatic oils; vegetable oils such as castor oil, linseed oil, and epoxidized soybean oil; and silicone oils and polyethylene waxes, etc., but not limited thereto. By adding these softeners in an amount of, for example, 0.5 to 5% by mass, particularly about 1 to 2% by mass, relative to the entire hollow plate-like core, the hollow plate-like core can be given flexibility, further improving the molding processability and mechanical strength of the entire laminated structure.

[0111] (Resins other than polypropylene-based resins and polyethylene-based resins)

[0112] Examples of resins other than polypropylene-based resins and polyethylene-based resins include:

[0113] Polyolefin resins such as polypropylene resins, polymethylpentene-1, and ethylene-cyclic olefin copolymers;

[0114] Polyamide resins such as nylon-6, nylon-6,6, nylon-6,10, nylon-6,12, etc.

[0115] Aromatic polyester resins such as polyethylene terephthalate and its copolymers, polyethylene naphthalate, and polybutylene terephthalate;

[0116] Polystyrene resins such as atactic polystyrene, syndiotactic polystyrene, acrylonitrile-styrene (AS) copolymer, acrylonitrile-butadiene-styrene (ABS) copolymer;

[0117] Polyvinyl chloride resins such as polyvinyl chloride and polyvinylidene chloride;

[0118] Polyphenylene sulfide;

[0119] Polyether resins such as polyethersulfone, polyetherketone, and polyetheretherketone, etc.

[0120] However, from the viewpoint of facilitating the effects of the present invention, it is preferred that the hollow plate-like core in the stacked structure of the present invention does not contain resins other than polypropylene-based resins and polyethylene-based resins, or even if it does, it is only a small amount (for example, less than 1.0% by mass relative to the entire hollow plate-like core).

[0121] As a colorant, any of the conventionally known organic pigments, inorganic pigments or dyes can be used. Examples of organic pigments include azo, anthraquinone, phthalocyanine, quinacridone, isoindolinone, dioxazine, perinone, quinophthalone and perylene pigments. Examples of inorganic pigments include ultramarine, titanium oxide, titanium yellow, iron oxide (red iron oxide), chromium oxide, zinc white and carbon black.

[0122] Examples of the antioxidant include phosphorus-based antioxidants, phenol-based antioxidants, and pentaerythritol-based antioxidants.

[0123] Examples of the flame retardant include halogen flame retardants, phosphorus flame retardants, and non-phosphorus and non-halogen flame retardants such as metal hydrates.

[0124] Examples of the blowing agent include aliphatic hydrocarbons (propane, butane, pentane, hexane, heptane, etc.), alicyclic hydrocarbons (cyclobutane, cyclopentane, cyclohexane, etc.), halogenated hydrocarbons (chlorodifluoromethane, difluoromethane, trifluoromethane, trichlorofluoromethane, dichloromethane, dichlorofluoromethane, dichlorodifluoromethane, chloromethane, chloroethane, dichlorotrifluoroethane, dichloropentafluoroethane, tetrafluoroethane, difluoroethane, pentafluoroethane, trifluoroethane, dichlorotetrafluoroethane, trichlorotrifluoroethane, tetrachlorodifluoroethane, perfluorocyclobutane, etc.), inorganic gases (carbon dioxide, nitrogen, air, etc.), water, etc.

[0125] [Method for manufacturing hollow plate-like core]

[0126] The hollow plate-like core in the laminated structure of the present invention can be produced, for example, by temporarily producing a sheet-like product using the above-mentioned components, bending the sheet-like product and then joining the sheet-like product by bonding, welding, mechanical sewing or the like.

[0127] A general sheet manufacturing method can be used in the manufacture of sheet-like objects. For example, it can be manufactured by mixing and melt-kneading the components, and molding into a sheet-like object / film-like object. The timing of mixing or melt-kneading can be appropriately set according to the molding method to be adopted (extrusion molding, injection molding, vacuum molding, etc.). For example, mixing can be carried out before feeding from the hopper of the molding machine or at the same time as molding. Melt-kneading can be carried out, for example, by a twin-screw mixer. In addition, the formation of the adhesive layer described later can also be carried out while manufacturing the hollow plate-like core sheet by a manufacturing method such as co-extrusion.

[0128] Next, the manufactured sheet is processed into a concavoconvex shape or a corrugated shape. For example, a hollow cylindrical core can be manufactured by giving the sheet a semicircular cylindrical concavoconvex shape and joining it with a similarly processed sheet. Alternatively, the sheet can be cut into a desired size, molded into a shape such as a hexagonal prism or a cylinder, and joined. From the viewpoint of simplicity, the joining is preferably performed by bonding or welding, and particularly preferably, the joining is performed by an adhesive or an adhesive layer.

[0129] (Adhesive)

[0130] There is no particular restriction on the adhesive that can be used in the manufacture of the hollow plate-like body core, and it can be selected from various general adhesives. As an example, polyester adhesives such as polyvinyl acetate or poly (methyl) acrylic acid (ester), ethylene-vinyl acetate copolymer (EVA) adhesives, modified polyolefin adhesives such as maleic anhydride modified polypropylene, polyamide adhesives, epoxy adhesives, polyurethane adhesives, polyolefin adhesives, polyvinyl chloride adhesives, terpene adhesives, phenolic resin adhesives, elastic system adhesives, such as hydrogenated products of styrene-butadiene copolymers or SEBS, natural rubber, chloroprene rubber, nitrile-butadiene copolymers, etc., but are not limited to these. A variety of adhesives can also be used in combination. In addition, these adhesives can also be formed into sheets or strips, for example, as the adhesive layer used for heat fusion.

[0131] <Surface Sheet>

[0132] The laminated structure of the present invention has a structure in which surface sheets composed of thermoplastic resin are attached to both sides of the above-mentioned hollow plate-like body core. Here, the thermoplastic resin is a polypropylene resin and / or a polyethylene resin. That is, the surface sheet in the present invention is composed of a polypropylene resin and / or a polyethylene resin. By having such surface sheets on both sides of the hollow plate-like body core, the laminated structure of the present invention becomes a structure with excellent physical properties such as lightness, mechanical strength, and heat insulation, and also good appearance.

[0133] Here, "composed of polypropylene resin and / or polyethylene resin" means that, for example, 95% or more by mass, further 97% or more by mass, and especially 99% or more by mass of the surface sheet is composed of polypropylene resin and / or polyethylene resin, and substantially does not contain other resins or inorganic powder fillers. It does not mean that a small amount of additives is excluded, and the aforementioned additives incorporated into the hollow plate-like core may also be incorporated into the surface sheet. For example, the surface sheet may also contain 0.1 to 2.0 parts by mass, especially 0.2 to 1.0 parts by mass of lubricants, plasticizers, antistatic agents and other processing aids, antioxidants and other anti-deterioration agents, colorants headed by carbon black or pigments, etc.

[0134] (Polypropylene resin / polyethylene resin for the surface sheet)

[0135] There is no limitation on the polypropylene resin and polyethylene resin constituting the surface sheet, and the same resins as the polypropylene resin and polyethylene resin as the core components of the hollow plate-like body can be used. For example, the same resins as the polypropylene resin and polyethylene resin selected as the core components of the hollow plate-like body can be used, and other types of polypropylene resins and polyethylene resins can also be used. It is also possible to use multiple types of polypropylene resins and / or polyethylene resins in combination, and it is also possible to make the two surface sheets of different materials.

[0136] In the laminated structure of the present invention, the thermoplastic resin constituting the surface sheet is preferably a polypropylene resin. That is, the surface sheet in the present invention is preferably a polypropylene resin sheet. The specific gravity of the polypropylene resin is generally lighter, so the advantages of the laminated structure of the present invention, which is lightweight and high in strength, are more significant. The surface sheet consisting of a polypropylene homopolymer is particularly preferred.

[0137] In addition, preferably, the MFR (230°C) of the polypropylene resin constituting the surface sheet is about 0.3 to 5.0 g / 10 minutes, and particularly preferably, the MFR (230°C) is 0.3 to 3.0 g / 10 minutes and the melt tension (230°C) is about 5 to 30 g. If the resin constituting the surface sheet is a resin having such melting characteristics, it has excellent bonding properties with the above-mentioned hollow plate-like body core, and the laminated structure of the present invention can be manufactured more easily.

[0138] 《Method for producing a laminated structure》

[0139] The laminated structure of the present invention can be manufactured from the above-mentioned hollow plate-like body core and the surface sheet by any known method. For example, the surface sheet can be welded on both sides of the hollow plate-like body core, or it can be attached using an adhesive. There is no particular limitation on the adhesive used here, and various known adhesives can be used. For example, the adhesive exemplified in the description of the manufacture of the hollow plate-like body core can be used. In addition, the surface sheet can also be attached to both sides of the hollow plate-like body core with the help of a commercially available double-sided adhesive sheet or a double-sided adhesive sheet. It is also possible to pre-apply an adhesive layer on one side or both sides of the surface sheet and perform heat fusion. The adhesive layer can be obtained, for example, by extruding two layers of a hot-melt adhesive and the surface sheet raw material.

[0140] 《Applications of laminated structures》

[0141] Although the laminated structure of the present invention is based on a general-purpose resin, it has high strength and is lightweight as a structural material. Therefore, it is useful as a building material or a material for a transporter such as an aircraft. Since the laminated structure of the present invention is based on a general-purpose resin, it is low in cost and has excellent formability. Therefore, it can be used as various people's livelihood products or industrial products such as various containers, daily necessities, consumables, and electrical and electronic parts.

[0142] "panel"

[0143] The laminated structure of the present invention also presents a good appearance, and is therefore particularly suitable for use as a panel. The panel of the present invention is lightweight, has high strength, and has a good appearance, and is therefore useful as a panel for interior decoration of a house or a store, a display panel in an activity venue, an advertising panel arranged on the outer wall of a building, etc. The panel of the present invention also has excellent heat insulation, and is therefore also suitable as a building material panel arranged on a ceiling or a wall. Since the core is composed of a hollow plate-like body, posters can also be simply attached using pushpins, etc. In addition, small holes can also be made on a part of the surface sheet to be used as a sound-absorbing panel. In addition, the hollow plate-like body core of the panel of the present invention contains a large amount of inorganic powder, and therefore also has the advantage of being flame retardant. From such an aspect, the panel of the present invention is also suitable for building materials or display boards, etc.

[0144] Example

[0145] Hereinafter, the present invention will be described in more detail with reference to Examples, but the present invention is not limited to these Examples.

[0146] [Example 1]

[0147] <Production of hollow plate-shaped body core>

[0148] Using an HTM50 counter-rotating twin-screw extruder (manufactured by CTE Corporation), 40.0 parts by mass of polypropylene resin-1, 60.0 parts by mass of heavy calcium carbonate-1 and 1.0 parts by mass of lauric acid diethanolamide (LEDA) were mixed to prepare raw material particles for hollow plate cores. The obtained raw material particles were then co-extruded from an extruder with a feed block-type T-die together with an adhesive resin, and rapidly cooled on a cooling roll to obtain a three-layer sheet with an inner layer thickness of about 0.36 mm and each outer layer (adhesive layer) thickness of about 0.02 mm. It should be noted that the characteristics of the raw materials used are as follows.

[0149] Polypropylene resin-1 (PP): propylene homopolymer, MFR (230°C): 0.5 g / 10 min

[0150] Heavy calcium carbonate-1 (CC-1): average particle size: 1.5 μm, specific surface area 1.5 m 2 / g, no surface treatment

[0151] Adhesive resin: Melthene (registered trademark) M (EVA base) manufactured by Tosoh Corporation.

[0152] The obtained 10 three-layer sheets were stacked by sandwiching a fixture consisting of a PTFE rod with a regular hexagonal prism of 4 mm on one side, and pressed at about 110°C. It should be noted that the fixture has the following structure, that is, 20 PTFE rods in each fixture are connected at one end to form a comb-like structure, and low-viscosity silicone oil is pre-sprayed on each PTFE rod before stacking. After the PTFE rod is extracted from the pressed body, it is cut into 20 mm wide to make a honeycomb core with a size of about 160×35×20tmm and a pitch of about 8mm.

[0153] <Production of Surface Sheet>

[0154] The polypropylene resin-1 and the above-mentioned adhesive resin are melted using a screw extruder, and after co-extrusion from a feed block-type T-die, they are quickly cooled on a cooling roller to obtain a two-layer sheet with a polypropylene layer thickness of about 0.40 mm and an adhesive layer thickness of about 0.02 mm.

[0155] <Production of Laminated Structure>

[0156] Two surface sheets were laminated on both sides of the hollow plate-like core obtained above with the adhesive layer facing the hollow plate-like core, and pressed at about 100° C. to produce a Figure 1 A stacked structure having the shape shown in a.

[0157] <Evaluation of Physical Properties of Laminated Structure>

[0158] The laminated structure produced as described above was evaluated for moldability and appearance according to the following criteria, and its bending strength was measured under the following conditions. The results of the evaluation and measurement are shown in Table 1 described below.

[0159] Forming processability

[0160] A: The hollow plate core can be formed into a target shape and is easy to cut into a honeycomb core. The honeycomb core will not be deformed when the surface sheets are stacked.

[0161] B: Although no obvious deformation of the honeycomb core occurs, it is not easy to make a hollow plate core or cut it into a honeycomb core from the three-layer sheet.

[0162] C: During the pressing process when the hollow plate-like core is produced and the surface sheets are laminated, flow in the three-layer sheet or deformation of the hollow plate-like core occurs.

[0163] Appearance

[0164] A: No defect or deformation was observed in the core of the hollow plate-like body.

[0165] B: A defect or deformation occurs in a part of the core of the hollow plate-like body.

[0166] C: The core of the hollow plate-like body is deformed significantly.

[0167] Bending strength

[0168] The measurement was performed at a speed of 2 mm / min using Autograph AG-100kNXplus (Shimadzu Corporation) under the conditions of 23°C and 50% RH in accordance with JIS K7171:2016.

[0169] [Comparative Example 1]

[0170] The same operation as in Example 1 was performed except that 100.0 parts by mass of polypropylene resin 1 and 1.0 parts by mass of lauric acid diethanolamide were used instead of heavy calcium carbonate 1 to prepare the three-layer sheet for the hollow plate core. The evaluation results are shown in Table 1 described below.

[0171] [Comparative Example 2]

[0172] The same operation as in Example 1 was performed except that the mass ratio of the polypropylene resin-1:the heavy calcium carbonate-1 was 60:40 to prepare the three-layer sheet for the hollow plate core. The evaluation results are shown in Table 1 described below.

[0173] [Comparative Example 3]

[0174] An attempt was made to produce a three-layer sheet for a hollow plate core using 7.0 parts by mass of polypropylene resin-1, 93.0 parts by mass of heavy calcium carbonate-1, and 1.0 parts by mass of lauric acid diethanolamide, but mixing / extrusion failed and the three-layer sheet for a hollow plate core itself could not be produced.

[0175] [Comparative Example 4]

[0176] The same operation as in Example 1 was performed except that the surface sheets were stacked in parallel with the arrangement direction of the honeycomb structure to produce a stacked structure in which the hollow plate-like bodies were arranged in the short side direction (direction of about 35 mm in size). The evaluation results are shown in Table 1 below.

[0177] [Example 2]

[0178] The same operation as in Example 1 was carried out except that 1.0 part by mass of polyoxyethylene alkylamine (POEA) was used instead of lauric acid diethanolamide. The evaluation results are shown in Table 1 described below.

[0179] [Example 3]

[0180] The same operation as in Example 1 was performed except that 30.0 parts by mass of polypropylene resin-2, 70.0 parts by mass of heavy calcium carbonate-2 and 0.5 parts by mass of lauric acid diethanolamide were used to prepare the three-layer sheet for the hollow plate core. The evaluation results are shown in Table 1 described below. The properties of the raw materials used in this example are as follows.

[0181] Polypropylene resin-2 (b-PP): block polypropylene (a structure in which polyethylene and ethylene-propylene copolymer blocks are dispersed in homopolypropylene), MFR (230°C): 0.5 g / 10 min

[0182] Heavy calcium carbonate-2 (CC-2): average particle size: 2.2 μm, BET specific surface area: 1.0 m 2 / g, no surface treatment

[0183] [Comparative Example 5]

[0184] The same operation as in Example 2 was attempted except that only 100.0 parts by mass of polypropylene resin-2 and 0.5 parts by mass of lauric acid diethanolamide were used to produce the three-layer sheet for the hollow plate-like body core instead of heavy calcium carbonate-2. Although the three-layer sheet was able to be produced, flow occurred in a part of the sheet when they were stacked and pressed, and the hollow plate-like body core of the target shape could not be produced.

[0185] [Example 4]

[0186] The same operation as in Example 1 was performed except that 20.0 parts by mass of polypropylene resin-1, 6.7 parts by mass of polyethylene resin-1, 3.3 parts by mass of polyethylene resin-2, 70.0 parts by mass of heavy calcium carbonate-1 and 0.5 parts by mass of lauric acid diethanolamide were used to prepare the three-layer sheet for the hollow plate core. The evaluation results are shown in Table 1 described below. It should be noted that the properties of the polyethylene resin used in this example are as follows.

[0187] Polyethylene resin-1 (PE-1): high-density polyethylene, density: 0.950g / cm 3 , MFR (190℃, 2.16kg): 7.5g / 10min

[0188] Polyethylene resin-2 (PE-2): linear low-density polyethylene, density: 0.918g / cm 3 , MFR (190℃, 2.16kg): 1.0g / 10min

[0189] [Example 5]

[0190] The same operation as in Example 1 was performed except that 20.0 parts by mass of polyethylene resin-1, 10.0 parts by mass of polyethylene resin-2, 70.0 parts by mass of heavy calcium carbonate-1 and 0.5 parts by mass of lauric acid diethanolamide were used to prepare the three-layer sheet for the hollow plate core. The evaluation results are shown in Table 1 below.

[0191] [Comparative Example 6]

[0192] The same operation as in Example 3 was attempted except that the three-layer sheet for the hollow plate-like body core was prepared by using only 66.7 parts by mass of the polyethylene resin-1, 33.3 parts by mass of the polyethylene resin-2, and 0.5 parts by mass of lauric acid diethanolamide instead of heavy calcium carbonate-1. Although the three-layer sheet was able to be produced, flow occurred in a part of the sheet when it was stacked and pressed, and a hollow plate-like body core of the target shape could not be produced.

[0193] [Comparative Example 7]

[0194] Polyethylene terephthalate (PET) was used instead of polypropylene resin-1, and the same operation as in Comparative Example 1 was performed. However, the three-layer sheet was pressed to form the hollow plate-like core at about 160°C. Although the molding temperature was increased compared with that in Example 1 or Comparative Example 1, it was difficult to obtain a hollow plate-like core of the target shape, and it was not easy to cut it into a honeycomb core. The evaluation results are shown in Table 1.

[0195] [Table 1: Proportions and evaluation results of the hollow plate core of each sample]

[0196]

[0197] *Unit: parts by mass ◎Lauryl diethanolamide

[0198] ※Polyoxyethylene alkylamine#Unit: MPa

[0199] As shown in Table 1, the stacked structures of Examples 1 to 5 according to the present invention are excellent in molding processability and good in appearance. In particular, in Examples 1 and 3 to 5 in which lauric acid diethanolamide is added, the hollow plate core is easy to make. On the other hand, the stacked structures of Comparative Examples 1, 5 and 6 that do not contain inorganic fillers have poor molding processability and poor appearance overall. The same tendency also exists in the stacked structure of Comparative Example 2 in which the mass ratio of resin: inorganic powder is 60:40. In addition, in Comparative Example 3 in which the amount of inorganic powder in the core of the hollow plate is greater than 90% by mass, (although not recorded in Table 1, as mentioned above) it is impossible to mold the sample itself.

[0200] The stacked structures such as Comparative Example 1, in which the ratio of the core of the hollow plate-like body does not meet the requirements of the present invention, have low strength even when a sample with a relatively good appearance is obtained. In addition, even if the ratio of the core of the hollow plate-like body is the same, when it is not arranged along the thickness direction of the stacked structure as in Comparative Example 4, the bending strength is significantly reduced.

[0201] Although the above-mentioned decrease in bending strength can be prevented by using PET as the resin component of the core of the hollow plate-like body as in Comparative Example 7, in this case, the moldability is reduced and it is difficult to say that the appearance is also good. On the other hand, the laminated structures of Examples 1 to 5 of the present invention, especially the laminated structure of Example 4 comprising a polypropylene resin, a polyethylene resin, heavy calcium carbonate and lauric acid diethanolamide, not only have good moldability and appearance, but also have high bending strength. This shows that the present invention has exerted a significant effect.

[0202] Description of Reference Numerals

[0203] 1: Laminated structure;

[0204] 2: Hollow plate body core;

[0205] 3: Surface sheet;

[0206] 4: Surface piece.

Claims

1. A laminated structure, which is a laminated structure formed by laminating surface sheets composed of a thermoplastic resin on both surfaces of a hollow plate-like body core, wherein the hollow plate-like bodies are arranged and arranged in the thickness direction in the hollow plate-like body core, wherein: The hollow plate-like core comprises polypropylene resin and / or polyethylene resin and inorganic powder, wherein the mass ratio of the polypropylene resin and / or polyethylene resin to the inorganic powder is 10:90 to 50:50, and The surface sheet is made of a polypropylene resin and / or a polyethylene resin.

2. The laminated structure according to claim 1, wherein The hollow plate-like body core contains lauric acid diethanolamide, and the content of the lauric acid diethanolamide is 0.1 mass % or more and 1.0 mass % or less relative to the total mass of the hollow plate-like body core.

3. The laminated structure according to claim 2, wherein: The polyethylene resin in the core of the hollow plate body comprises high-density polyethylene and linear low-density polyethylene, and the mass ratio of the high-density polyethylene to the linear low-density polyethylene is 90:10 to 50:

50. The melt mass flow rate, i.e., MFR, of the high-density polyethylene measured at 190°C and 2.16kg according to Japanese Industrial Standard JIS K 6922-1, i.e., according to International Organization for Standardization Standard ISO1133 is 5 g / 10 minutes or more and 15 g / 10 minutes or less. The MFR of the linear low-density polyethylene measured at 190°C and 2.16kg according to Japanese Industrial Standard JIS K 6922-1, i.e., according to International Organization for Standardization Standard ISO1133 is 0.5 g / 10 minutes or more and 1.5 g / 10 minutes or less.

4. The laminated structure according to claim 2, wherein: The polypropylene-based resin of the hollow plate-like core is a polypropylene homopolymer and / or a propylene block polymer.

5. The laminated structure according to claim 1, wherein The hollow plate-like core contains both the polypropylene-based resin and the polyethylene-based resin.

6. The laminated structure according to claim 1, wherein The surface sheet is a polypropylene resin sheet.

7. The laminated structure according to claim 1, wherein The inorganic substance powder is heavy calcium carbonate.

8. The laminated structure according to claim 7, wherein: The average particle size of the heavy calcium carbonate is greater than or equal to 0.7 μm and less than or equal to 6.0 μm.

9. The laminated structure according to claim 1, wherein: The hollow plate-like core and the surface sheet are bonded together via an adhesive layer.

10. The laminated structure according to claim 1, wherein The hollow plate-like body core is selected from the group consisting of a honeycomb core, a hollow cylindrical core, a wave-type corrugated core and a harmonica-shaped core. 11 . A panel comprising the laminated structure according to claim 1 .

Citation Information

Patent Citations

  • Building decorative panel and execution thereof

    JP1994320652A

  • Molding and method for producing the same

    JP2010247448A

  • Multilayer structure

    JP2013233796A

  • Container

    JP2017065810A

  • Laminate structure

    JP2018108740A